Nanocarriers From Natural Lipids With In Vitro Activity Against Campylobacter jejuni - Ribeiro, Lígia Nunes de Morais; de Paula, Eneida; Rossi, Daise Aparecida; Martins, Flávia Alves; de Melo, Roberta Torres; Monteiro, Guilherme Paz; Breitkreitz, Márcia Cristina; Goulart, Luiz Ricardo; Fonseca, Belchiolina Beatriz (Frontiers in Cellular and Infection Microbiology, 2021)
Campylobacter jejuni (CJ) is the most prevalent zoonotic pathogen of chicken meat and related products, which may lead to gastroenteritis and autoimmune diseases in humans. Although controlling this bacterium is important, CJ strains resistance against traditional antibiotic therapy has been increased. Vegetable oils and fats are natural biomaterials explored since the Ancient times, due to their therapeutic properties. Nanotechnology has promoted the miniaturization of materials, improving bioavailability and efficacy, while reducing the toxicity of loaded active molecules. In this work, a screening of 28 vegetable oils was firstly performed, in order to select anti-CJ candidates by the disc diffusion test. Thus, the selected liquid lipids were used as active molecules in nanostructured lipid carriers (NLC) formulations. The three resultant systems were characterized in terms of particle size (~200 nm), polydispersity index (~0.15), and zeta potential (~-35mV), and its physicochemical stability was confirmed for a year, at 25°C. The structural properties of NLC were assessed by infrared (FTIR-ATR) and differential scanning calorimetry (DSC) analyses. The spherical nanoparticle morphology and narrow size distribution was observed by transmission electron microscopy (TEM) and field emission scanning electron (FE-SEM) analyses, respectively. Then, the in vitro antimicrobial activity test determined the minimum inhibitory concentration (MIC) of each formulation against CJ strains, in both free (1–3 mg/ml−1) and sessile (0.78 mg/ml−1) forms. Finally, the in vitro biocompatibility of NLC was demonstrated through cell viability using VERO cell line, in which F6 was found twice less cytotoxic than pure olibanum oil. Considering the abovementioned achieved, F6 formulation is able to be evaluated in the in vivo anti-CJ efficacy assays.